Reading violence: representation and ethics - Thompson, Allan Campbell (My University, 2009)
ABSTRACT The textual representation of an instance of violence involves three principle considerations: a notion of representation, a conception of violence, and an inter-relationship between ethical and aesthetic evaluations. By investigating these considerations within the context of postmodern thought, a more sensitive perception of textual representations of violence becomes possible. Any representation, prior to being read and interpreted, has no predetermined meaning, and therefore no inherent value. It is only through a process of reading that verifiability, the principles of appraisal and personal cognition become actualised. As any text is necessarily iterable – subject to infinite (re)interpretation within an infinite number of future contexts – any interpretation is determined by the intersection of the iterable text and the historically situated reader. Violence, which is defined as an act of direct or indirect intentional harm against a person’s body or mind or property, may be experienced either as an event, or as a representation of an event. In instances of the representation of violence, the ethical perspective of the reader is influenced to a large extent by expectations of the text’s verifiability, the linguistic register of the text, and the inter-subjective ethical framework at the moment of reading the text. The aesthetic evaluation of the narrative, which is closely associated with its linguistic features, is also closely related to this ethical perspective. However, normative systems of ethics are often inadequate in the face of the plurality of meaning and possibilities inherent in representations of violence, and therefore a postmodern conception of ethical thought seems most appropriate. Textual instances of violence therefore have the potential for representing a multiplicity of experiences and ethical responses, without necessarily having to rely upon problematic normative obligations of systemisation or duty. A recognition of postmodern ethical ambiguity, combined with a flexibility of moral outlook, allows the reader to develop a more nuanced approach to the ethical predicaments suggested by the representation of violence.
Keywords: postmodern ethics; normative ethics; representation; text; iterability; reader; fiction; non-fiction; violence; Holocaust